Strategi Pengembangan Human Capital melalui Program Manajemen Talenta di PT PLN (Persero) Unit Induk Pembangunan Sumatera bagian Selatan - Hilma Harmen; Alifya Dzihni Innayah C; Dian Putri Islami Br Sebayang; Jhonatan Fidei Lafau; Nabila Al Zahra Ginting; Oktaviane Situmorang; Shella Anjelika Br Tampubolon; Siti Yusriah; Tesya Lola Otovia (Universitas Nusantara PGRI Kediri, 2026)
This study aims to formulate a human capital development strategy through the implementation of a talent management program at PT PLN (Persero) South Sumatra Main Development Unit. Changes in the business environment, digitalization, and increasingly competitive job market demand organizations to manage human capital more systematically and sustainably. This study uses a literature review method by reviewing scientific journals, books, and official documents related to talent management and human resource development. The results of the study indicate that the implementation of the talent management program at PT PLN has not been optimal due to several obstacles, such as mismatching employee placement with competencies, unequal access to training, lack of socialization, and weak job succession planning. Based on these findings, recommended development strategies include the implementation of a digital-based competency assessment system, ongoing training and certification, strengthening the talent pool and succession planning, improving internal communication, and instilling a work culture oriented towards performance and innovation. The implementation of this strategy is expected to increase the effectiveness of talent management, strengthen the quality of human capital, and support organizational sustainability in facing the national energy transformation.